PERANAN MASYARAKAT NELAYAN DALAM AKTIVITAS KEPARIWISATAAN DI PANTAI JEMELUK DESA PURWAKERTI KECAMATAN ABANG KABUPATEN KARANGASEM - Aristiarini, Putu Lilis; Mahagangga, I Gusti Agung Oka (JURNAL DESTINASI PARIWISATA, 2015)
Abstract Indonesia is well-known as a maritime for centuries. Lots of Indonesian work as fishermen. Not to mention in Bali, eventhough tourism now become a prospective sector to work in, but in several coastal point, people still work as a fisherman. These people are strong and open-minded, they usually easy to accept new concept. In East of Bali, at Karangasem Regency, fishermen collaborate marine tourism with their natural work in a great way.This is the phenomenon that occurs and interesting to be observed. In this paper, I use qualitative method as a main reseach frame. To get a valid data, depth interview was already applied. The result shows that particularly in Amed Beach, fishers who become members of Kelompok Nelayan (Fishers Group) Mina Prami finally formed specific group to organize tourism activity especially marine tourism. They specifically contributed to help provide a mode of transportation for tourists who want to do marine tourism activities such as diving, snorkeling and fishing. Fishermen has strong bond between one and other that formed since long time ago. They help each other without considering the benefit or loss they would get. Eventhough they are in same work field, everybody has their own job in society after go to the sea. Various roles of fishing communities in tourism can support the local economy and support alternative tourism in the area of East Bali.
Keywords: Role, fishermen, activity, tourism